Penataan Masterplan Bukit Doa Maria Watu Blencong Sebagai Upaya Pengembangan Wisata Religi Inklusif dan Berkelanjutan - Yustina Banon Wismarani; Mutiara Cininta; Sebastianus Adjie Sindhunata; Michael Grace Susanto (Jurnal Atma Inovasia, 2025)
This community service activity aims to design a master plan for the Watu Blencong Maria Prayer Hill area in Kalibawang, Kulon Progo, as an inclusive, safe, and spiritually meaningful Catholic pilgrimage site. This area has strong natural potential in the form of hilly contours, sacred natural stones called Watu Blencong, and unique light orientation, but has not been arranged functionally and symbolically. The design approach was carried out through a participatory method involving parish administrators, congregations, and the local community in three stages of discussion forums (initial, interim, and final reports). The main concept developed was "Light, Stone, and Hill", which was translated into a zoning system, spiritual circulation, and devotional elements based on the natural landscape. The result is a master plan that integrates the Stations of the Cross path, devotional places, reflective spaces, and supporting facilities while maintaining the ecological character of the site. This master plan not only optimizes the spiritual experience of the congregation by creating a contemplative space but also opens opportunities for the development of community-based religious ecotourism.